A miRNA-binding-site SNP of MSX1 is Associated with NSOC Susceptibility. (June 2014) - Ma, L.; Xu, M.; Li, D.; Han, Y.; Wang, Z.; Yuan, H.; Ma, J.; Zhang, W.; Jiang, H.; Pan, Y.; Wang, L.
MSX1 is a favorable candidate gene for susceptibility to non-syndromic orofacial clefts (NSOCs). However, the roles of MSX1 genetic variants in the development of NSOC are controversial and vary among human populations. In the present study, the roles of 4 potentially functional single-nucleotide polymorphisms (SNPs) of MSX1 (rs12532 in 3′-untranslated region [UTR], and rs3821947, rs3821949, and rs4464513 in 5′ upstream) were investigated in a case-control study of 602 NSOC cases and 605 healthy controls. The findings showed that rs12532 located within 3′-UTR of MSX1 could influence the risk of developing NSOC. Individuals who carried the variant genotype (rs12532AA genotype) showed a decreased possibility of developing NSOC (AA vs . GG: OR = 0.69, 95% CI = [0.49, 0.98]). Interestingly, similar effects were also observed on cleft lip with palate (CLP), in a stratified analysis (allelic comparison-12532A allele vs . 12532G allele, OR = 0.80, 95% CI = [0.66, 0.99]; genotypic comparison-AA vs . GG, OR = 0.58 95% CI = [0.37, 0.91]). Sequence analysis indicated that this SNP might alter the binding ability of miR-3649, confirmed by luciferase activity assay showing a lower expression level of rs12532 A allele compared with that of the G allele ( p < .001 for 293A and COS7 cell lines). Furthermore, an in vivo study showed that MSX1 expression among individuals carrying the AA genotype of rs12532 was markedly lower than that in those with the GG genotype, while the inverse correlation was observed for miR-3649, thus providing a possible interaction between MSX1 and miR-3649 in the etiology of NSOC. Taken together, these findings indicate that SNPs in the miRNA-binding sites might play an important role in the development of NSOCs. Furthermore, if confirmed in subsequent studies, the polymorphisms may be considered as additional markers for the evaluation of infants' risk of NSOCs.